Land use Land cover change Assessment at Cement Industrial area using Landsat data-hybrid classification in part of YSR Kadapa District, Andhra Pradesh, India - Sudhakar, C. Venkata; Reddy, G. Umamaheswara (International Journal of Intelligent Systems and Applications in Engineering, 2022)
India is the world’s second-largest cement manufacturer. It is a significant contributor to the Indian economy’s GDP. Kadapa district is one of Andhra Pradesh’s largest cement producers. Limestone and cement plant sediment and mine have local, regional, and global impacts on soil, vegetation, and water and air quality. As a result, mapping and change evaluation of the mining area are critical for the sustainability of the cement industry. With today’s advancements in remote sensing technology, mapping the Earth’s characteristics, observing environmental changes, and controlling natural resources become more efficient with less human efforts than conventional methods. Proposed work focused on land environment temporal change assessment in YSR kadapa district, Andhra Pradesh, India over a period from 1991 to 2019. The results of Landsat-5/7/8 image Hybrid classification using ERDAS IMAGINE and ArcGIS over the study area 684KM2 showing an overall accuracy 92 % and kappa index 0.9 in comparison to conventional methods of classification.